Performance trends for operational intelligence through value chain model - Kaula, Rajeev (Journal of Advanced Computer Science & Technology, 2016)
Value chain is a successful management model for improving business competitiveness. A value chain based analytic approach facilitates meaningful grouping of business processes such that appropriate value from business operations can be derived. As organizations focus on competitive advantage and growth, a value chain derived operational intelligence provides insight to compete successfully in the marketplace. This paper outlines an approach to develop performance based value metrics in the form of analytic business rules for operational intelligence through the value chain model. The paper illustrates the concepts through a University value chain prototype which is implemented in Oracle’s PL/SQL language.